EVALUATION OF ANTIOXIDANT CAPACITY AND TOXICITY OF CHRYSANTHEMUM FLOWER (Chrysanthemum morifolium) EXTRACT - Malano, Zahra Khoirunissa; Hendrawan, Siufui; Ferdinal, Frans (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2025)
The increasing trend of air pollution has worsened the air quality and deteriorated human health. This situation subsequently causes the accumulation of free radicals, leading to oxidative stress, and eventually the emergence of various diseasessuch as. respiratory and degenerative disorders. Indonesia is home to a wide variety of plantsthat may posses medicinal beneficial and efficacy. Chrysanthemum (Chrysanthemum morifolium) is one of the most commonly found flowers and is known to containphytochemicals. Therefore, this research aimed to determine the antioxidant activity and toxicity level of Chrysanthemum morifolium flower extract. In brief, chrysanthemum flowers were dried and extracted, screened for phytochemical content, and tested for antioxidant activity using the Ferric Reducing Antioxidant Power (FRAP) methods. Toxicity assay was determined using the Brine Shrimp Lethality Test. The results showed that the chrysanthemum ectract contained several phytochemicals, including alkaloids, flavonoids, terpenoids, betacyanins, and phenolics.The antioxidant activity test yielded an IC50 value of 11.13 μg/mL, inidicating a very strong antioxidant activity. Meanwhile the toxicity test showed an LC50 value of 15.49 μg/mL. In conclusion, chrysanthemum flowers exhibit very strong antioxidant activity and have potential as an antimitotic agent. Keywords: antioxidant, chrysanthemum flower, phytochemicals, toxicity assay DOI : 10.35990/mk.v8n4.p366-377